(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Along with various microorganisms that enter the body from the external environment, there are also microorganisms that live in symbiosis with it in the human body, forming the normal human microflora. They are located in various biotopes and are important for the functioning of the body. One of such biotopes is the large intestine, the normal microflora of which, consisting of indigenous and facultative microorganisms, is of great importance for vital activity. As is known, the microbiocenosis of the large intestine consists of more than 450 microorganisms and participates in the metabolism of the "host" organism and the formation of colonization resistance in the intestine.